Calculation of the equivalent electrical parameters of the inductor of induction channel furnace with defects in its lining - Podoltsev, O.D.; Zolotaryov, V.M.; Shcherba, M.A.; Belyanin, R.V. (Електротехніка і електромеханіка, 2018)
Aim. The aim of the paper is to determine a quantitative relationship between measured impedance of the inductor and the
electrical characteristics of the separated melt circuit parts for the determination of the place of a liquid metal leakage and for the
improvement in such way the diagnostic system of lining state of induction channel furnaces. Technique. The study was
performed on the basis of the concepts of theoretical electrical engineering, mathematical physics, and mathematical modeling.
Results. Using two equivalent electrical circuits of the inductor the analytical expressions and graphical dependencies, which
determine a quantitative relationship between the parameters of the separated parts of a liquid-metal circuit and the impedance of
the whole inductor measured in practice, for the presence of different lining defects, were found. The method for calculating the
increments of equivalent electrical parameters of the inductor as a function of increments of the parameters of the secondary
liquid-metal circuit was proposed. Scientific novelty. It is proved that for small changes (less than 10 %) of the parameters of the
liquid-metal circuit, it is expedient to use a linear relationship between its increments and to create the sensitivity matrix, which
clearly shows the presence of a strong or weak interrelation between the disturbed values of the parameters of the secondary
circuit and the inductor. Practical significance. The use of this technique allows to develop the database for various types of
lining defects for a given furnace and on its basis to predict the places of a melt leakage and the state of furnace lining owing to
periodical measurements of the inductor parameters. Цель. Целью статьи является установление количественной связи между измеряемым импедансом индуктора и
электрическими характеристиками отдельных участков контура расплава для установления места протекания
жидкого металла и усовершенствования таким образом системы диагностики состояния футеровки индукционных
канальных печей. Методика. Для проведения исследований использовались положения теоретической
электротехники, математической физики, математического моделирования. Результаты. C использованием двух
электрических схем замещения индуктора получены аналитические выражения и графические зависимости,
устанавливающие количественную связь между параметрами отдельных участков жидкометаллического контура и
измеряемым на практике импедансом всего индуктора при наличии различных дефектов в его футеровке.
Предложена методика расчета приращений эквивалентных электрических параметров индуктора в зависимости от
приращений параметров вторичного жидкометаллического контура. Научная новизна. Доказано, что при малых
изменениях (менее 10%) параметров жидкометаллического контура целесообразно использовать линейную связь
между их приращениями с построением матрицы чувствительности, которая наглядно показывает наличие сильной
или слабой связи между возмущенными значениями параметров вторичного контура и индуктора. Практическое
значение. Использование данной методики позволяет разработать базу данных для различных типов дефектов
футеровки для индукционной канальной печи и на ее основе, путем периодического измерения параметров индуктора,
прогнозировать места протеканий расплава и состояние футеровки.